Resisting the Carceral: The need to align anti-trafficking efforts with movements for criminal justice reform - Swenstein, Abigail; Mogulescu, Kate (Anti-Trafficking Review, 2016)
Response to ATR Debate Proposition: ‘Prosecuting trafficking deflects attention from much more important responses and is anyway a waste of time and money’